Export Growth Drivers in the EU - Nitescu, Dan Costin; Dragomir, Maria Cristina; Murgu, Valentin; Turcan, Ciprian Sebastian; Bunea, Mariana (Transformations In Business & Economics, 2026)
The article addresses the issues of identifying the impact of the independent indicators analyzed (i.e. insurance and financial services, gross capital formation, transport services, foreign direct investment, research and development expenditure, changes in inventories and inflation) at the level of the 22 European economies over a period of 23 years. The evolution of goods and merchandise exports, were considered dependent indicators. According to our findings within the econometric study, higher volume related to the exported goods and merchandise are associated with high levels of insurance, gross capital formation, transport services, FDI, R&D expenditure and inventories. Our analysis confirms that significant increase in prices due to cost-push inflation can negatively impact trade by making exports less competitive in international markets. Conversely, efforts to address trade imbalances through cost reduction measures may result in economic distress. Therefore, maintaining a balanced approach to inflation and trade policies is essential to ensuring overall economic stability. We have identified that clusters of EU countries having lower inflation, like North-Western European countries, tend to have higher trade activity. In the same time, the South Eastern-European countries show lower overall values, which might indicate developing or smaller economies. These results add value to the existing literature, concluding and formulating recommendations for policy support, to contribute and increase exports competitiveness both at the EU level and for South Eastern European.